2024
DOI: 10.1002/iid3.1203
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inflammatory cytokines and in‐hospital complications of acute pancreatitis

Jiaxin Yao,
Shuangshuang Zhang,
Fei Zhou
et al.

Abstract: ObjectiveAcute necrotic collection (ANC), acute peripancreatic fluid collection (APFC), pleural effusion, and ascites are common early complications of acute pancreatitis. This study aimed to investigate the relationship between 12 serum cytokines and the early complications and severity of acute pancreatitis (AP).MethodsWe retrospectively analyzed the clinical data of 307 patients with AP, and divided them into severe group and mild‐to‐moderate group according to the revised Atlanta classification. Propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recently Corti et al 32 reported that the differential S-nitrosoglutathione (GSNO) catabolism mediated by GGT enzyme activity can downregulate the production of IL-8, which is a NF-κB target. Consistently, IL-8 levels were associated with pancreatitis risk 33 . Therefore, the role played by GGT1 in the metabolism of endogenous GSNO may also deserve attention insofar as the possibility exists that selected polymorphisms of the GGT1 enzyme are associated with lower activation of this endogenous anti-inflammatory molecule, as suggested previously 34 .…”
Section: Discussionmentioning
confidence: 74%
“…Recently Corti et al 32 reported that the differential S-nitrosoglutathione (GSNO) catabolism mediated by GGT enzyme activity can downregulate the production of IL-8, which is a NF-κB target. Consistently, IL-8 levels were associated with pancreatitis risk 33 . Therefore, the role played by GGT1 in the metabolism of endogenous GSNO may also deserve attention insofar as the possibility exists that selected polymorphisms of the GGT1 enzyme are associated with lower activation of this endogenous anti-inflammatory molecule, as suggested previously 34 .…”
Section: Discussionmentioning
confidence: 74%